2002
DOI: 10.1142/s021797920200941x
|View full text |Cite
|
Sign up to set email alerts
|

IN SITU CHARACTERISATION OF CALCITE GROWTH AND INHIBITION USING ATOMIC FORCE MICROSCOPY

Abstract: Real time in situ monitoring of calcite growth and inhibition on the cleavage plane (1014) is investigated using atomic force microscopy (AFM). Calcite growth and inhibition were studied using a Molecular Imaging microscope in contact mode, equipped with an in situ fluid cell. As has been reported previously, it is observed that calcite growth from aqueous solution is by motion of mono-molecular steps, and dissolution by a combination of step motion and etch pit expansion. The measured step heights were betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
1

Year Published

2005
2005
2010
2010

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 20 publications
2
23
0
1
Order By: Relevance
“…Experimental observations of calcite surfaces [12,54] show a high density of steps, where carbonate dissolution at the pH of interest (around nine) is more favorable [55], which is also predicted by theory [56]. Even stable surfaces such as the ð1 0 1 4Þ surface have been shown to reconstruct in moist air via pit formation and film growth [57], making it reasonable to consider defective stepped surfaces in our simulations.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…Experimental observations of calcite surfaces [12,54] show a high density of steps, where carbonate dissolution at the pH of interest (around nine) is more favorable [55], which is also predicted by theory [56]. Even stable surfaces such as the ð1 0 1 4Þ surface have been shown to reconstruct in moist air via pit formation and film growth [57], making it reasonable to consider defective stepped surfaces in our simulations.…”
Section: Resultssupporting
confidence: 61%
“…One way to gain this level of control is the use of growth modifying additives during the precipitation of calcite from the aqueous phase. It has been shown in the past that the adsorption of many types of polymers such as hydrophilic block copolymers [6,7], polycarboxylic acids [8][9][10][11], phosphonates [12,13] and polyamino acids [14][15][16][17] during precipitation or dissolution can modify calcite particle size and morphology. It was also shown that polycarboxylic acids can promote a very particular growth mechanisms [18], during which agglomeration of small primary particles results in a very high overall specific surface area.…”
Section: Introductionmentioning
confidence: 99%
“…Work within our group has focused on trying to understand, at a fundamental level, the interactions of inhibitor molecules with the surfaces of barium sulfate [4][5][6][7]. In addition, we have sought to take useful information from molecular modelling and see whether it correlates with inhibition and vice versa, thus undertaking several studies employing both computational and experimental techniques [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…At low concentrations, the adsorption of phosphate and phosphonate on calcite has been studied in detail [3][4][5][6][7][8][9][10][11][12][13][14][15]. Several in situ atomic force microscope (AFM) [3][4][5]15] and X-ray photoelectron spectroscopy [6] studies showed that phosphonate and phosphate are adsorbed to the growth sites (kink 0021-9797/$ -see front matter  2004 Elsevier Inc. All rights reserved. doi:10.1016/j.jcis.2004.08.054 site, step edges, and terraces) and further growth of calcite is therefore inhibited.…”
Section: Introductionmentioning
confidence: 99%